Adverse effects of energy restriction on changes in immunoglobulins and complements during weight reduction in judoists - Umeda, T.; Nakaji, S.; Shimoyama, T.; Kojima, A.; Yamamoto, Y.; Sugawara, K. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: A preliminary study to investigate the combined effects of dietary restriction and weight reduction through exercise on markers of immune function in college judoists before and after a single competition. METHODS: Forty-nine judoists participated in the study. Thirty-eight athletes combined exercise and dietary restriction (WR group), and 11 athletes did not require dietary restriction (EX group). Changes in anthropometric parameters, energy intake, concentrations of serum immunoglobulins and complements, and white blood cell counts were assessed at 4 time points: 20 days (pre-values), 4 days and 1 day before the competition, and 7 days after the competition. RESULTS: Compared with pre-values, the WR group exhibited significant decreases in body weight (-2.8 kg at 1 day before) and fat free mass (-1.7 kg at 1 day before); there were no changes in these variables in the EX group. The WR group exhibited significant decreases in IgG, IgM and C3 at 7 days after the competition (all p<0.01). In the EX group, significant decreases in IgM and C3 (both p<0.05) were observed at 7 days after the competition, though to a lesser degree than in the WR group. CONCLUSIONS: Energy restriction seemed to exacerbate alterations in immune markers such as immunoglobulin and complement induced by vigorous exercise at 7 days after a competition. Although the changed values were still within normal limits, we hypothesize that the potential cumulative effect of these changes over many competitions in 1 year might well induce abnormal levels with a possibly harmful clinical effect on judoists.